Eating Fire While Walking on Broken Glass: An Auto-Ethnography of One Adult Educator's Tenure Process - Dianne Ramdeholl (Adult Education Research Conference, 2016)
This autoethnography documents the journey of one female academic of color through her tenure process, outlining the landmines embedded within the tenure process for women of color. It offers recommendations for new faculty of color.
Keywords: critical race theory; autoethnography.